2013
DOI: 10.1074/jbc.m112.427302
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Peptide of the Tumor-shared Antigen Midkine Hosts CD4+ T Cell Epitopes

Abstract: Background: The CD4 T cell response to the tumor antigen Midkine was unknown. Results: Most of the T cell response to Midkine relies on T cell epitopes contained in its signal peptide. Conclusion:The signal peptide of Midkine is accessible to HLA class II pathway for CD4 T cell presentation. Significance: It is a new function for signal peptides to contribute to tumor-specific CD4 T cell response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…We can ascribe this strong and broad immune response to the lipophilic sequences within SP domains, such as MUC1‐SP‐L, which has been shown by us (Kovjazin et al , ,b, ; Kovjazin & Carmon, ) and others (Wilkinson et al , ; Kerzerho et al , ) to be more immunogenic than other protein domains, and which, in the case of ImMucin, can generate a rapid response, using a low dose of naked LP administered in conjunction with hGM‐CSF, without employing a dedicated ‘carrier system’ or specific adjuvants. In contrast, other anti‐MUC1 vaccination strategies primarily induce humoral responses and/or selected CD8+ T‐cell activation in a subset of patients (Roulois et al , ).…”
Section: Discussionmentioning
confidence: 80%
“…We can ascribe this strong and broad immune response to the lipophilic sequences within SP domains, such as MUC1‐SP‐L, which has been shown by us (Kovjazin et al , ,b, ; Kovjazin & Carmon, ) and others (Wilkinson et al , ; Kerzerho et al , ) to be more immunogenic than other protein domains, and which, in the case of ImMucin, can generate a rapid response, using a low dose of naked LP administered in conjunction with hGM‐CSF, without employing a dedicated ‘carrier system’ or specific adjuvants. In contrast, other anti‐MUC1 vaccination strategies primarily induce humoral responses and/or selected CD8+ T‐cell activation in a subset of patients (Roulois et al , ).…”
Section: Discussionmentioning
confidence: 80%
“…All of the donors mounted a CCNB1-specific T cell response. By comparison with tumor Ags that we have already investigated by this approach, this response was qualified as very good (8,40). This frequency is in the range of that observed for NY-ESO-1 (0.5-5 cells/M), which is considered as one of the prototype tumor Ags for the development of cancer vaccine (21).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, T-cell lines induced ex-vivo against these SP domains, using both naive and patient-derived PBMCs, demonstrated an effector memory profile (CD45RO C CD44 C CD62L high ), coupled with robust antigenspecific IFN-g production, as well as cytotoxic properties against MUC1-positive tumor 45 and MTb-infected cells. 46 Similarly, these SP domains induced a strong and specific cellular immune response [45][46][47] and anti-tumor activity 45 in both mice and in a firstin-human study. 48 More recently, an additional support for the potency of SP domains was published by Kerzerho et al, which demonstrated the existence of multiple CD4…”
Section: Antigen-specific Cd4mentioning
confidence: 99%
“…We attribute the strong immune response observed with SP domains to the following factors: first, SP domains contain hydrophilic/lipophilic sequences which are known to be more immunogenic, mainly with regard to T-cell induction (by enhancing MHC binding and cell penetration), which, in select cases, is comparable to that achieved when administering a vaccine with incomplete Freund's adjuvant 53 (and authors unpublished data). Second, as indicated, SP domains demonstrate promiscuous binding to MHC class I, mainly via TAP-independent presentation, and to MHC class II 47 and also present a high density of B-cell epitopes, which seemingly underlie the observed preferred dual T/ B-cell immunogenicity. 8,54,55 Based on the limited available information on combining SP domains with different adjuvants in human studies, it is too early to predict if a given mixture will effectively reduce the amount of required antigen and/or the quality of the response.…”
Section: Generation Of Humoral Immunitymentioning
confidence: 99%